Challenges in implementing and maintaining osteoporosis therapy - Modi A; Sajjan S; Gandhi S (Dove Medical Press, 2014)
Ankita Modi,1 Shiva Sajjan,1 Sampada Gandhi2 1Center for Observational and Real-World Evidence, Merck & Co., Inc., Whitehouse Station, NJ, USA; 2School of Public Health, Rutgers University, Piscataway, NJ, USA Abstract: In the United States, an estimated 19% of older men and 30% of older women are at elevated risk of osteoporotic fracture and considered to be eligible for treatment. The burden of osteoporosis is similar in Europe and is projected to rise worldwide, with aging populations and increasing fracture rates accompanying urbanization. Notwithstanding its high prevalence, osteoporosis is often underdiagnosed and undertreated. Moreover, even when the diagnosis is made and the decision is taken to treat, there are remaining challenges in implementing therapy for osteoporosis. Several patient populations are particularly challenging for clinicians to treat and require further study with regard to osteoporosis therapy. These include the very elderly, who face challenges relating to adherence; men, in whom osteoporosis remains under-recognized; patients with glucocorticoid-induced osteoporosis or renal impairment, who are at increased risk of fracture; patients with preexisting gastrointestinal problems who cannot tolerate existing orally administered osteoporosis therapies; and high-risk patients who show inadequate response to therapy. Moreover, poor adherence and poor persistence with osteoporosis medications are common and result in an increased risk of fracture, higher medical costs, and increased hospitalizations. Once the decision to institute therapy is made, patient education about osteoporosis and fracture risk should be provided. This is particularly important for men, who may not be aware that osteoporosis can be a concern. Secondary prevention programs, including fracture liaison services and bone therapy groups, can help to improve adherence to therapy. Further study is needed to guide the treatment of men, the very elderly, patients with glucocorticoid-induced osteoporosis and renal impairment, high-risk patients not well-controlled despite therapy, and patients with preexisting gastrointestinal conditions. Moreover, therapies are needed that are viewed as effective and safe by both physicians and patients, and as convenient to take by patients. Keywords: adherence, chronic kidney disease, glucocorticoid-induced osteoporosis, fracture